2004
DOI: 10.1152/ajpheart.00734.2003
|View full text |Cite
|
Sign up to set email alerts
|

Saturated glucose uptake capacity and impaired fatty acid oxidation in hypertensive hearts before development of heart failure

Abstract: Abnormalities in energy metabolism may play an important role in the development of hypertensive heart failure. However, the transition from compensated hypertrophy to heart failure is not fully understood in terms of energy metabolism. In Dahl salt-sensitive (DS) and salt-resistant (DR) rats, myocardial fatty acid and glucose uptake values were determined using (131)I- or (125)I-labeled 9-methylpentadecanoic acid ((131)I- or (125)I-9MPA), and [(14)C]deoxyglucose ([(14)C]DG), fatty acid beta-oxidation was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
0
11
1
Order By: Relevance
“…Recent studies [18,[22][23][24] and the present study, however, clearly demonstrated the existence of cardiac metabolites of methyl-branched fatty acid analogs processed via α-and β-oxidations. As seen in Fig.…”
Section: Effect Of Ipccontrasting
confidence: 51%
See 1 more Smart Citation
“…Recent studies [18,[22][23][24] and the present study, however, clearly demonstrated the existence of cardiac metabolites of methyl-branched fatty acid analogs processed via α-and β-oxidations. As seen in Fig.…”
Section: Effect Of Ipccontrasting
confidence: 51%
“…Recent animal studies [18,[22][23][24], however, demonstrated that β-oxidation metabolites of fatty acid analogs with methyl branch, i.e., BMIPP and 9MPA, were detected in coronary venous samples or myocardium, and the amount of β-oxidation metabolites was affected by changes in energy substrate and myocardial disorder. In a metabolic process of BMIPP, α-oxidation is initially required for further metabolic process.…”
Section: Mpa Uptake and Its Intracellular Metabolism In Ischemia-repmentioning
confidence: 99%
“…13 The Dahl salt-sensitive rat, a model that develops hypertension and LVH with salt feeding that progresses to heart failure, 14 has reduced fatty acid uptake, which occurs before loss of systolic function. 15,16 This genetic model with dietary trigger does not require surgery to implant an aortic band and results in consistent hypertension and LVH. In the present investigation, we assessed the effect of a highfat diet on LV function and the development of LVH.…”
Section: Introductionmentioning
confidence: 93%
“…There is evidence that administration of propionyl-L-carnitine increases both glucose and palmitate oxidation in hypertrophied hearts and improves the efficiency of translating ATP production into cardiac work. On this basis, a restoration of metabolic demand by restoring mitochondrial energy efficiency may have potential as a new therapeutic treatment of the hypertensive heart and heart failure (Fujii et al, 2004). Although as yet no agent exists that promote mitochondrial biogenesis, PGC-1 alpha has generated interest.…”
Section: Emerging Therapy Targeting Mitochondrial Energeticsmentioning
confidence: 99%